MODEL KEPEMIMPINAN PARTISIPATIF DALAM PEMBERDAYAAN MASYARAKAT DAN DESA PARTICIPATIVE LEADERSHIP MODEL IN ENDEAVORING SOCIETY AND VILLAGE - Sayogo, Budi (Pembangunan Pedesaan, 2006)
Local leadership was demanded to have a number of capacities so that they can be able to conduct their roles and functions as changing and reforming agensiats in any community. Some of those capacities were articulative, aspirative, and accommodative capabilities toward the adjacent developing social dynamic. Therefore, the local leader for their own credibility must be will do and able to be actively involved in initiative form for every substantially and strategically decision maker activity at the local level.